2002
DOI: 10.1889/1.1830801
|View full text |Cite
|
Sign up to set email alerts
|

5.4: A Defect Free Bistable C1 SSFLC Display

Abstract: A defect free, large memory angle, high contrast ratio and bistable C1 SSFLC display, which has potential for E-paper and Liquid Crystal on Silicon (LCoS) applications has been developed using 5 o oblique SiO deposition alignment. The electro-optical properties and bistability of this display have been investigated. Various aspects of defect control are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 9 publications
2
8
0
Order By: Relevance
“…Geometrically, a zigzag free C1 structure can be achieved with 5 o obliquely evaporated SiO alignment 7,8,9 . However, this device still generally shows some subtle defects 10,11 , such as those reported before, are seen also in the SmA phase. One defect we found in our SiO aligned cell is the pin defect (Figure 1), which is related to the spacers and the dust, and it looks like a meteor.…”
Section: Results and Discussion 31supporting
confidence: 69%
See 1 more Smart Citation
“…Geometrically, a zigzag free C1 structure can be achieved with 5 o obliquely evaporated SiO alignment 7,8,9 . However, this device still generally shows some subtle defects 10,11 , such as those reported before, are seen also in the SmA phase. One defect we found in our SiO aligned cell is the pin defect (Figure 1), which is related to the spacers and the dust, and it looks like a meteor.…”
Section: Results and Discussion 31supporting
confidence: 69%
“…We eliminated this defect by mixing the spacers in the UV-curable glue instead of spraying spacers onto the entire substrate and properly controlling the etching condition. The pin defects are removed and the contrast ratio was improved significantly 10 . The textures of the cell before and after removing the spacers from the pixel region for both materials are also shown in Figure 1.…”
Section: Results and Discussion 31mentioning
confidence: 99%
“…Another important property of LC-surface interactions, especially for FLC alignment [3,4], is pretilt (Figure 2(b)). Molecular orientation at a surface can vary from perpendicular (90° pretilt) to parallel (0° pretilt).…”
Section: Alignment Direction and Pretiltmentioning
confidence: 99%
“…It has been found that the high pretilt angle of obliquely deposited SiO X can be used to suppress C2 chevron formation in ferrroelectric liquid crystal (FLC) devices, thus eliminating zigzag defects [2]. Combined with the low threshold bistable switching of some FLCs on SiO X , this makes SiO X an attractive candidate for use in commercial devices [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…True bistable switching is achieved with relatively few FLC/alignmentsurface combinations. In particular, obliquely deposited SiO X and SiO 2 alignment surfaces have been shown to produce low voltage bistable switching with some FLCs [5][6][7], making them good candidates for use in FLCOS devices. We utilize these alignment surfaces with newly developed FLC materials to make experimental bistable FLCOS devices.…”
Section: Introductionmentioning
confidence: 99%